PRAKTEK SEHAT YANG BERPENGARUH TERHADAP KESEHATAN MENTAL PADA LANJUT USIA - Elfian Zulkarnain (Jurnal Ilmu Kesehatan Masyarakat, 2015)
According to international demographic data from the Bureau of the Census, USA in 1993, the increase in the number of elderly Indonesia between the years 1990 to 2025 reached 414%, the highest in the world. The rapid increase was related to the life expectancy of the population of Indonesia. This study aimed to analyze the various factors of healthy practices in influencing mental health in the elderly and examines the factors which contributed to the biggest and the smallest to the mental health of the elderly in Lumajang. This study uses analytic research with quantitative approach. The samples in this study using a multistage random sampling technique, carried out in urban, sub-urban and rural with a sample of 378 respondents. Location by dividing into three areas, namely urban (sub-district Puskesmas Labruk-Lumajang,) sub urban (sub-district Puskesmas Tekung-Tekung) and rural (Puskesmas Padang-Padang District). Data collection using structured interviews, and analyzed using confirmatory factor analysis. All variables affect the healthy practice of mental health in the elderly significantly (p <α). The highest contributor indetermining the healthy mental aspect is able to solve complex problemswhile the lowest contributors are recreation periodically. To be able to obtain a good healthy status, it is necessary to be a lifestyle practice recreationperiodically and efforts to retain the memory of the way the brain vitalization gymnastics as necessary for the elderly in supporting mental healthKeyword: healthy practices, mental health , elderly